"Blackness" is an index of redox complexity in melanin polymers. Issue 31 (13th July 2020) - Manini, Paola; Lino, Valeria; D'Errico, Gerardino; Reale, Samantha; Napolitano, Alessandra; De Angelis, Francesco; d'Ischia, Marco
Abstract : Blackness as an emergent property associated with redox disorder and π-electron complexity in melanin polymers. Abstract : Disclosed herein is the first experimental evidence for a direct correlation between the broadband visible light absorption ("blackness") and the coexistence of reduced and oxidized substructures in a set of model polymers from isomeric dihydroxynaphthalenes structurally related to fungal melanin (mycomelanin) from 1, 8-dihydroxynaphthalene. Excellent linear plots ( r 2 = 0.97 and 0.94) were determined between the integrals of featureless absorbance curves over the 400–800 nm range, the electron spin density values in the EPR spectra and the width of selected oligomer peak clusters in the MALDI-MS spectra. Blackness, which is shown to be strongly interrelated with electron spin density, is thus proposed herein as a robust index of redox inhomogeneity and electron complexity reflecting the shift of oligomer populations toward highest oxidation states.